Forging Paths: A Systematic Review on the Interplay of Government Policies, Technological Advancements, and Business Growth through the Role of Economic Innovation. - Riwayadi, Eko; Umran, M. Fankar; Murti, Tri Hesti; Monoarfa, Maya; Waisapi, Jeffry Yuliyanto; Cahyono, Bambang Tri (MultiTech Publisher, 2024)
The 21st-century global economic landscape is characterized by unprecedented complexity, shaped by the dynamic interplay of government policies, technological advancements, economic innovation, and business growth. This systematic review, anchored in established economic theories such as the Innovation Systems Theory and the Triple Helix Model, seeks to unravel the intricate relationships among these key elements. Findings reveal a consistent pattern where government policies exert significant influence on the pace and direction of technological advancements. Economic innovation emerges as a crucial mediating factor, linking policy influence to subsequent impacts on business growth. Noteworthy themes include the role of regulatory frameworks, the importance of collaboration for innovation, and the varied pathways through which technological advancements contribute to business growth. The alignment of results with the conceptual framework underscores the relevance and validity of the identified relationships. Theoretical implications enrich established economic theories, while practical insights empower businesses to navigate evolving government policies through strategic innovation and adaptability. This systematic review contributes a comprehensive understanding of the interconnected dynamics shaping the contemporary economic landscape, offering a valuable roadmap for informed decision-making and sustained growth.